2013
DOI: 10.1097/ccm.0b013e31828a44ed
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IKKβ in Enterocytes Exacerbates Sepsis-Induced Intestinal Injury and Worsens Mortality

Abstract: Objective NF-kB is a critical regulator of cell survival genes and the host inflammatory response. The purpose of this study was to investigate the role of enterocyte-specific NF-kB in sepsis through selective ablation of IkB kinase (IKK)-ß. Design Prospective, randomized, controlled study. Setting Animal laboratories in university medical centers. Subjects and Interventions Mice lacking functional NF-kB in their intestinal epithelium (Vil-Cre/Ikkßf/Δ) and wild type (WT) mice were subjected to sham lapar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 58 publications
1
33
0
Order By: Relevance
“…It has been shown that the inhibition of NF-κB is significantly correlated with improvement of survival from endotoxin shock and sepsis. 38,39 Our results further demonstrate that 5-MTP blocks NF-κB by interrupting p38 MAPK signaling pathway. Although signaling kinases such as p38 MAPK and ERK1/2 are activated and involved in TLRmediated responses, 17,18,40 5-MTP selectively suppresses p38 but not ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 67%
“…It has been shown that the inhibition of NF-κB is significantly correlated with improvement of survival from endotoxin shock and sepsis. 38,39 Our results further demonstrate that 5-MTP blocks NF-κB by interrupting p38 MAPK signaling pathway. Although signaling kinases such as p38 MAPK and ERK1/2 are activated and involved in TLRmediated responses, 17,18,40 5-MTP selectively suppresses p38 but not ERK1/2 activation.…”
Section: Discussionsupporting
confidence: 67%
“…TSLP has been shown to induce signal transducer and activator of transcription (STAT) 1, STAT3, STAT4, STAT5, and STAT6 phosphorylation in human DCs, whereas it only activates STAT5 in mouse DCs (37,39 The down-regulatory effects of TSLP on inflammation may not be limited to its direct effects on myeloid cell function. Recent studies indicate that injury is associated with increased inflammation and worsens mortality in septic mice that do not express the transcription factor, NF-kB, in their intestinal epithelium (41). Injury is also one of the main triggers for TSLP production by epithelial cells (10), which requires the activation of the NF-kB signaling pathway (42).…”
Section: Discussionmentioning
confidence: 99%
“…A complementary approach demonstrating the importance of intestinal epithelial apoptosis and permeability involved transgenic mice lacking functional Nuclear Factor kappa B (NFkB) in their intestinal epithelium (75). When sepsis in induced in these animals via CLP, both intestinal epithelial apoptosis and permeability are greater than is seen in wild type septic animals, associated with an increase in claudin 2 levels.…”
Section: Intestinal Failure In Sepsismentioning
confidence: 99%